PENERAPAN METODE PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN IPAS MATERI PERKEMBANGBIAKAN TUMBUHAN PADA PESERTA DIDIK KELAS IVD SD NEGERI 47 PALEMBANG - Ina Nofiana Joyo Boyo; Hudaidah; Helen Saputri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to examine how effective the Contextual Learning (CL) strategy used in class 4D is in improving learning outcomes in the Plant Growth course in the Natural and Social Sciences (IPAS) course. A total of 32 students participated in the study conducted at SDN 47 Palembang. The research approach used is called Classroom Action Research (CAR) and is divided into two cycles with stages of planning, implementation, observation, and reflection in each cycle. The results of the study showed that the use of the CL strategy significantly improved students' learning objectives. Between Cycle I and Cycle II, the average student score increased significantly from 60 in the pre-cycle to 70 and 80 in Cycle II. Thus, it is evident that the Contextual Learning methodology improves students' understanding of plant growth in class 4D. This study recommends contextual learning as a useful strategy to improve training standards, especially in the IPAS subject.